Upaya penurunan stunting melalui pola asuh dengan pelatihan pembuatan “Nugget Mayur” sebagai makanan tambahan - Mahilda, Ardelia Elvia; Yulianti, Dede; Arum, Dewi; Fitriyani, Lisa; Ariyani, Diyah (Nur Science Institute, 2024)
Stunting is a problem associated with chronic malnutrition over a long period caused by not fulfilling a balanced intake of nutrients, where children in the process of growth and development experience disorders such as short height conditions (dwarfism), which means they do not develop as other children in general. In this case, parenting patterns are fundamental because parenting patterns that are less supportive regarding nutrition and health care for children can increase the risk of stunting. Therefore, parents must innovate to meet children's nutritional needs and build healthy eating habits. The service implementation carried out by UIN Salatiga's Community Service Students (KKN) is to guide parents in Losari Village, Sumowono District, Semarang Regency, in supporting children's development with balanced parenting management. Implementing the service is through training in making